2018
DOI: 10.1080/14756366.2017.1419217
|View full text |Cite
|
Sign up to set email alerts
|

Design and synthesis of naphthalimide group-bearing thioglycosides as novel β-N-acetylhexosaminidases inhibitors

Abstract: GH20 human β-N-acetylhexosaminidases (hsHex) and GH84 human O-GlcNAcase (hOGA) are involved in numerous pathological processes and emerged as promising targets for drug discovery. Based on the catalytic mechanism and structure of the catalytic domains of these β-N-acetylhexosaminidases, a series of novel naphthalimide moiety-bearing thioglycosides with different flexible linkers were designed, and their inhibitory potency against hsHexB and hOGA was evaluated. The strongest potency was found for compound 15j (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(51 citation statements)
references
References 35 publications
1
49
0
Order By: Relevance
“…They tested their inhibitory activity toward hOGA and lysosomal β-hexosaminidases of different origins. [120][121][122] Structure-activity relationship studies suggested that a linker of five to seven atoms between the two moieties would be favorable for selectively targeting hOGA. [121] Inhibitor 21 a has a moderate inhibitory activity towards hOGA (K i = 3.8 μM) and exhibits some degree of selectivity over HexB.…”
Section: Thioglycoside-naphthalimide Hybridsmentioning
confidence: 99%
“…They tested their inhibitory activity toward hOGA and lysosomal β-hexosaminidases of different origins. [120][121][122] Structure-activity relationship studies suggested that a linker of five to seven atoms between the two moieties would be favorable for selectively targeting hOGA. [121] Inhibitor 21 a has a moderate inhibitory activity towards hOGA (K i = 3.8 μM) and exhibits some degree of selectivity over HexB.…”
Section: Thioglycoside-naphthalimide Hybridsmentioning
confidence: 99%
“…The results indicated that the hydrogen atom of NH in the 2-acetamido group of 13b could establish key interactions with the catalytic residues G67 and W278 via hydrogen bonds and the 4-bromonaphthalimide moiety of 13b rotated to the residue W679 to form a strong π−π stacking interaction as compared to 15b. 25 These interactions may have resulted in the 4-fold increase in hOGA inhibitory potency when compared with 15b 25 and 13b. For the binding mode of 13r ( Figure S6e), a significant conformational difference relative to 15b 25 and 13b could be observed.…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 99%
“…The naphthalimide moiety with a larger 4-piperidyl group of 13r moved into the new hydrophobic domain, which was composed of F223, E677, P678, F681, and W679, and the piperidyl group could then establish van der Waals interactions with E677 and P678 ( Figure S6e). In addition, affected by the 4-piperidylnaphthalimide moiety, the glycosyl moiety in 13r entered more deeply into the hOGA pocket and the conformation of glycosyl rotated clockwise around 80°, relative to the glycosyl moiety in 15b 25 (Figure 2c). Consequently, the key interactions could be observed due to the formation of hydrogen bonds between the catalytic residue N313 and the hydrogen atom in NH of the acetamido group in 13r ( Figure S6e).…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 99%
See 2 more Smart Citations